Evaluation of the use of a needle-free injection syringe as a cause of non-specific reactions in the intradermal tuberculin test used for the diagnosis of bovine tuberculosis. (August 2018) - Díez-Guerrier, A.; Roy, A.; de la Cruz, M.L.; Sáez, J.L.; Sanz, C.; Boschiroli, M.L.; Romero, B.; de Juan, L.; Domínguez, L.; Bezos, J.
Abstract: The objective of the study was to elucidate whether the use of the needle-free Dermojet syringe, which is based on a high pressure inoculation and is used to inject tuberculin in cattle in several countries, may, in itself, cause skin reactions that can be interpreted as positive reactions to the intradermal tests that are not, in fact, related to the real infection status of the animals. Forty-four cattle from an officially tuberculosis-free (OTF) herd were selected, and four single intradermal tuberculin (SIT) tests were performed on each animal, two on each side of the neck. Three different Dermojet (D1, D2 and D3) and one McLintock (M4) syringes were used to carry out sterile phosphate buffer saline (PBS) with 10% of glycerol and bovine PPD injections. No positive reactions to the SIT test were observed when using the D1-D3 syringes in the case of either bovine PPD or PBS. With regard to M4 (PBS), all the tests were negative when using a standard interpretation but three were positive in the case of the severe interpretation. Significant differences (p < 0.05) in the skin fold thickness measured were found only between certain Dermojet and McLintock syringes at certain inoculation sites. The results showed that the needle-free Dermojet syringe used for PPD intradermal testing in cattle did not cause significant reactions that could be misunderstood as positives. Highlights: First study evaluating the use of needle-free syringes as a cause of non-specific reactions on the skin test. Dermojet syringe did not cause in itself skin reactions that can be interpreted as positives. A low proportion of inconclusive reactors was detected when McLintock syringe was used. Significant differences on the results were detected between certain syringes at certain inoculation sites.